A heat-melt adhesive-assisted transferable electrode films - Yuki Maruyama (Nature Portfolio, 2021)
Abstract This report is the first on heat-assisted transferable battery components, enabling manufacturing batteries on non-planer surfaces such as a curved surface and an edge. The transferrable battery components were composed of two layers: a cathode or an anode and a conductive heal-melt adhesive layer on a silicone-based flexible supporting paper. These mechanically-durable, flexible components enabled conformable adhesion even on curved surfaces and substrate edges. As a model battery, the manganese dioxide-zinc system was constructed on a curved surface using transfer techniques and showed a practical capacity of 1.8 mAh cm−2 per unit electrode area. These transferable electrodes allow arbitrary design of batteries according to the power consumption of IoT devices to be fabricated on unreported geometries where has been considered as a dead space.